Blending Traditional and Modern Methods A New Curriculum Framework for PAI - Habib Zainuri (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
The background of this research is the need to develop a curriculum for Islamic Religious Education (PAI) that integrates traditional and modern teaching methods to enhance the quality of religious education in the digital era. This research aims to design a holistic PAI curriculum framework that retains traditional moral values while leveraging modern technology and pedagogy. The research method used is action research, involving an in-depth literature review and the implementation of the curriculum model in several schools as case studies. The findings show that integrating traditional and modern methods in the PAI curriculum can deepen religious understanding and develop 21st-century skills in students, such as digital literacy and critical thinking. The conclusion of this research is that the proposed PAI curriculum can address the challenges of religious education in the modern era, provide practical guidance for educators, and significantly contribute to innovation in Islamic education. Thus, it is hoped that young generations will be equipped with the moral integrity and adaptive capabilities needed to face technological advancements and global